6 Analysis of 983 civilian blast and ballistic casualties and the generation of a predictive model of injury burden. Issue 2 (23rd March 2023) - Maitland, Laura; Veen, Harald; Harrison, David; Baden, James; Hettiaratchy, Shehan
Abstract : Introduction: Wars, such as in Ukraine, as well as terror attacks cause blast and ballistic casualties that are unusual in civilian practice. The immediate surgical response has not been systematically characterised due to the unpredictable, stochastic nature of such mass casualty events. We studied how the military trauma system managed civilian casualties during the Afghanistan conflict (2009-2014), to quantify and assess the surgical response to blast and ballistic injuries managed in a developed world paradigm and may be a tool for Emergency Preparedness, Resilience and Response (EPRR) planning. Method: Throughout the Afghanistan conflict (2009–2014) data was gathered prospectively by surgical teams at the UK-led military Medical Treatment Facility, Camp Bastion, Afghanistan. A total of 10, 891 consecutive surgical cases were catalogued. Civilian cases were identified that had primary trauma surgery for blast and ballistic injuries and these formed the focus of this study (n=983). Statistical analyses with z-tests, significance was accepted at the 5% level (p<0·05). Results Paediatric wounding patterns when compared to adults show that children suffered consistently significantly more head (36·9% ;29·4%) and abdominal trauma (52·5%; 60·3%) for blast and ballistic injuries respectively (blast: 26·5%, z-2·263; p<0·05; 43·6%, z=-1·758, p<0·05; ballistic: 11·8%, z=2·926, p<0·01; 8%, z=-4·992; p<0·001; 60·3%, z=2·071, p<0·05). The three most common surgical procedures for blast injuries were debridement, amputation and laparotomy. For ballistic injuries, these were debridement, laparotomy and vascular procedures. A scalable predictive model of injury burden for blast and ballistic injuries in both adults and children is presented. Conclusion: This evidenced based, predictive model of the immediate response required to manage civilians injured by blast and ballistic mechanism can be applied to the conflict in Ukraine and to prepare for terror attacks on mass urban populations where blast and ballistic injuries are commonplace.